Sustainable Strategies for the Conservation and Utilization of Wild Medicinal Plant Resources in Karakalpakstan - Bibinaz Tileumuratova,; Nadira Mirametova,; Gulparshin Kutlimuratova,; Gozzal Taumuratova,; Luiza Bakhieva, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The conservation and sustainable use of wild medicinal plants are essential for preserving biodiversity and supporting traditional healthcare systems. Karakalpakstan, known for its rich plant biodiversity, faces environmental challenges such as climate change, habitat loss, and overharvesting, which threaten its medicinal flora. This study explores sustainable strategies for conserving and utilizing these plants. Key approaches include community-based conservation, habitat restoration, legal protection, and sustainable harvesting. Research involved field surveys, interviews with local communities, and consultations with experts. The findings show that community participation, traditional knowledge, and specific legal arrangements are the keys to successful conservation. Recommendations include community-led approaches, habitat rehabilitation, and tighter controls on harvesting. Policy recommendations involve stakeholder coordination, capacity building, and economic incentives to ensure that any conservation efforts in Karakalpakstan are long-lasting. These measures would be important for biodiversity protection, the support of local livelihoods, and global conservation concerns.